EFFECT OF USING ANIMATED VIDEO IN IMPROVING STUDENTS VOCABULARY MASTERY AT SDIT DARUSSALAM ISLAMIC SCHOOL SELESAI - Sakira Az Zahra; Maitri Rahmadhani; Edi Suprayetno (Edumaniora : Jurnal Pendidikan dan Humaniora, 2025)
This research the effectiveness of animated videos in improving the vocabulary mastery of third-grade students at SDIT Darussalam Islamic School Selesai. By using pre-experimental method, 16 students were assessed through Pre-tests and post-tests. The results showed a significant difference before and after the treatment. This was proven by the mean score increasing from 28.12 (pre-test) to 84.62 (post-test), while the T-test value (11.9) exceeded the T-table value (1.753). This indicates that the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. The cumulative percentage of the 20-item positive and negative statement questionnaire was 99.19%, with a total score of 1,349 that indicating students' responses to learning vocabulary using animated videos were in the very strong category. Therefore, animated videos proved highly effective in improving students' English vocabulary mastery as well as their interest in learning vocabulary using this media